Psikologi Komunikasi dalam Penerapan Nilai-Nilai Keislaman di Keluarga - Ismail (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2018)
Communication is the process of delivering information with a specific purpose and purpose. In psychology communication is also very important role as a tool to explore and understand who will be invited to communicate, then combined into a communication psychology. the purpose and purpose of this paper is to explain how the role of Communication Psychology in the application of Islamic values in the family. This discussion covers the pattern of communication within the family between husband and wife. Children and parents, older brothers and sisters by referring to Al-Qurran and Hadith.